2009
DOI: 10.1038/oby.2008.621
|View full text |Cite
|
Sign up to set email alerts
|

Development of Overweight in Children in Relation to Parental Weight and Socioeconomic Status

Abstract: The purpose of the study was to test the hypothesis that socioeconomic status (SES) moderates the association between parental weight and changes in BMI from childhood to early adolescence. Participants included 428 twin children from 100 families with obese parents (“obese families”) and 114 sociodemographically matched families with normal‐weight parents (“lean families”) who were assessed in their homes (age = 4.4). Follow‐up study was conducted 7 years later (age = 11.2) on 346 children (81%). Complete dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 28 publications
8
80
1
Order By: Relevance
“…Additionally, child measures of height and weight were measured objectively by trained researchers, eliminating the chance of parents under or overestimating their child's measurements. A limitation of our study, and numerous similar studies, 5,8,18 is the use of self-reported parent height and weight measurements. However, it has been suggested that for this age range there is only a modest discrepancy between self-reported and actual weight.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, child measures of height and weight were measured objectively by trained researchers, eliminating the chance of parents under or overestimating their child's measurements. A limitation of our study, and numerous similar studies, 5,8,18 is the use of self-reported parent height and weight measurements. However, it has been suggested that for this age range there is only a modest discrepancy between self-reported and actual weight.…”
Section: Discussionmentioning
confidence: 98%
“…These data reflect a genesocial environment interaction and suggest that adolescents exposed to an unfavourable environment will develop more severe obesity if they present an unfavourable genetic background. Childhood obesity has been unambiguously linked to lower educational levels and low parental social class, 53,54 and the influence of social factors can seem very early in life. 55 Unhealthy habitsFsuch as high-fat diets, low levels of physical activity and exposure to chronic stressFare seen more frequently in families with a low SES.…”
Section: Discussionmentioning
confidence: 99%
“…Hui et al (14) and Scaglioni (15) , for example, found that children of overweight parents had a higher risk for overweight. Next to parental overweight, socio-economic status (SES) has been identified several times as a risk factor for childhood overweight (15)(16)(17)(18)(19) . Income, paternal/maternal employment and paternal/ maternal educational level are often used as indicators of SES.…”
mentioning
confidence: 99%